Happiness, growth, and public policy - Richard A. Easterlin (Institute for the Study of Labor (IZA), 2013)
If society's goal is to increase people's feelings of well-being, economic growth in itself will not do the job. Full employment and a generous and comprehensive social safety net do increase happiness. Such policies are arguably affordable not only in higher income nations but also in countries that account for most of the population of the less-developed world. These conclusions are suggested by an analysis of a wide range of evidence on happiness in countries throughout the world.
Keywords: I31; I38; O21; F20; D60; E60; 330; happiness; life satisfaction; subjective well-being; economic growth; safety net policies; developed countries; transition countries; less developed countries; China